2009
DOI: 10.1007/978-3-642-00202-1_26
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized Complexity of Stabbing Rectangles and Squares in the Plane

Abstract: Abstract. The NP-complete geometric covering problem Rectangle Stabbing is defined as follows: Given a set of horizontal and vertical lines in the plane, a set of rectangles in the plane, and a positive integer k, select at most k of the lines such that every rectangle is intersected by at least one of the selected lines. While it is known that the problem can be approximated in polynomial time with a factor of two, its parameterized complexity with respect to the parameter k was open so far-only its generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Using this new combination, we are also able to resolve another open question [11,12], namely whether Disjoint Rectangle Stabbing is fixed parameter tractable.…”
Section: Cochromatic Numbermentioning
confidence: 99%
See 4 more Smart Citations
“…Using this new combination, we are also able to resolve another open question [11,12], namely whether Disjoint Rectangle Stabbing is fixed parameter tractable.…”
Section: Cochromatic Numbermentioning
confidence: 99%
“…In [12], the authors prove a W[1]-hardness result for a higher dimensional version of the Rectangle Stabbing problem and show several restrictions of this two dimensional version fixed-parameter tractable. Recently, Dom et al [11] and Giannopoulos et al [22] independently considered the general two dimensional version, the Rectangle Stabbing problem, and showed it to be complete for the parameterized complexity class W [1]. Dom et al [11] also showed that the restriction of Disjoint Rectangle Stabbing to b-Disjoint Square Stabbing, when all the rectangles are squares of the size b × b, is NP-complete for any fixed b ≥ 2.…”
Section: Disjoint Rectangle Stabbingmentioning
confidence: 99%
See 3 more Smart Citations